Development of musical taste in public school music education: do we really need Western trends? (Training and Practice : Journal of Educational Sciences, 2019)
To involve popular music inschool music education is not an unknown phenomenon in Western European Countries. Education in the first ten years play crucial role in human cognitive development. At the same time the majority of our pupils meet valuable musical materialsonly at public schools. This is the reason, why popular music should never get an exclusive place in the tuition of primary-school aged children. Theoretical background of my paper are Kodaly’s sentences. I intend to support my hypothesis by the means of a questionnaire among primary school-teachers and pupils coming from different social and geographical background.